Improved activity of W-modified MnOx-TiO2 catalysts for the selective catalytic reduction of NO with NH3 - Wang, X.; Li, X.; Zhao, Q.; Sun, W.; Tade, Moses; Liu, S. (2016)
The performances of a series of W-modified MnOx–TiO2 catalysts were investigated for selective catalytic reduction (SCR) of NOx with NH3. The catalyst prepared by one-pot co-precipitation method with an elementary ratio of W:Mn:Ti = 0.25:0.25:0.5 in raw materials showed a highest activity and a widest operation temperature window with 100% NOx conversion within 80–280 °C. We suggest that the enhancement in reducibility of manganese and dominant active Mn4+ species is likely one predominant factor accounting for the excellent SCR performance of the best catalyst. In situ FTIR studies revealed that after W doping, more Brønsted and Lewis acid sites formed on the catalyst surface, as well as more active intermediates (monodentate nitrate) during reaction, are also responsible for the high activity both at low and medium temperatures.